Evidence and evolution of magnetic polaron in HgCr2Se4 investigated by electron spin resonance. (4th June 2018) - Li, Lailai; Yan, Li-Qin; Shi, Youguo; Lu, Peipei; Sun, Young
Abstract: The evidence and evolution of magnetic polarons (MPs) in HgCr2 Se4 have been studied by electron spin resonance (ESR), magnetism and conductivity measurements in a temperature range of 5–300 K. A single paramagnetic resonance line is observed in the high-temperature range while multiple resonance lines appear in the low-temperature range. As temperature decreases, the peak-to-peak linewidth Δ H pp shows a minimum at T min ≈ 210 K, with the activation energy fitted by small polaron hopping model consistent with the bottleneck mechanism, providing an evidence for existence of small MPs above T min . The analysis of the temperature dependence of Δ H pp, double integrated intensity I, and g factor of ESR signals, combined with the temperature dependence of magnetization and conductivity, reveals an evolution process from small MPs at zone I ( T > T min ) to correlated MPs at zone II ( T c < T * ⩽ T ⩽ T min ) in the paramagnetic regime. Three critical temperatures, T min (≈210 K), T th (≈175 K), and T * (≈121 K), which determine the evolution characteristics of MPs, are distinguished. The magnetic correlation length ξ of Cr 3+ –Se 2− –Cr 3+ should account for the evolution of MPs.